Risk factors for cervical cancer - Cieza, Julio (2015)
OBJECTIVE: To identify risk factors of uterine cervical cancer. DESIGN: Retrospective descriptive study at the Gynecology and Obstetrics Department of Chiclayo Las Mercedes Teaching Regional Hospital, from january 1995 through march 1996. Files from the Registry of Gynecological Cancer were reviewed, including 110 patients with diagnosis of cervical cancer. Cervical biopsy was confirmed by pathology in 95% of cases. RESULTS: Median age was 47 years, 38,2% cohabited, 41% came from Chiclayo and districts. 68 women had not had previous Papanicolaou smear, age of first sexual relation was 18,4 years, 21% had more than one sexual partner, number of children was 6,4 and 73,3% presented advanced cancer (II, III, IV). Early star of sexual relations and high number of children were risk factors and number of sexual partners needs to be evaluated. CONCLUSIONS: This cancer is a public health problem, as 77,3% were in advanced stages, only 41% came from Chiclayo and 61,8% had never had a Pap smear.